Modelling manufacturing process using a modified IDEF0 framework a case study of a car door manufacturing plant - Al-Turki , Abdullah; Faris, Waleed Fekry (Inderscience Publishers, 2010)
This research paper explores a modified framework for the modelling of a manufacturing process. A modified IDEF0 model has been followed as the methodology since it can ease access to decision details from an unstructured database. From the case study, the concepts enable to build a full information model for decision-making in a manufacturing system to support basic production activities (operations, transport, inspection, etc.). The results obtained after the simulation of the modified model was found to be remarkable when it was verified with factory personnel.